2019
DOI: 10.3390/polym12010014
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Pervaporation Properties of PVA-Based Membranes Modified with Polyelectrolytes. Application to IPA Dehydration

Abstract: In this work, dense and supported pervaporation polyvinyl alcohol (PVA)-based membranes modified with poly(allylamine hydrochloride) (PAH) and poly(sodium 4-styrenesulfonate)(PSS)/PAH top nanolayers were synthesized. Two main points were investigated: the role of the polyelectrolyte PAH on water selectivity of the selective polymer matrix and the impact of the porous substrate based on polyacrylonitrile (PAN) and aromatic polysulfone amide (UPM-20 ® ), used to get supported high-performance membranes. Various … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 54 publications
(100 reference statements)
1
32
0
Order By: Relevance
“…One of the wide spread approaches to carry out the surface modification by LbL is via dip-LbL method. In our previous studies [ 15 , 32 , 33 ] it was demonstrated that changing various parameters of LbL assembly such as the selected pair of polycation–polyanion, the order of their deposition, the number of cycles, and additional bulk modification of membranes significantly affected the transport characteristics of the membranes.…”
Section: Introductionmentioning
confidence: 99%
“…One of the wide spread approaches to carry out the surface modification by LbL is via dip-LbL method. In our previous studies [ 15 , 32 , 33 ] it was demonstrated that changing various parameters of LbL assembly such as the selected pair of polycation–polyanion, the order of their deposition, the number of cycles, and additional bulk modification of membranes significantly affected the transport characteristics of the membranes.…”
Section: Introductionmentioning
confidence: 99%
“…PAH, SA, and PSS were used as polyelectrolytes (PEL) in the form of solutions with the concentration of 10 −2 mol/L. The membrane was fixed in the device and alternately immersed in polyelectrolyte solutions for 10 min, and washed in water between them [ 68 ]. First, a membrane is immersed in polyanion solution of the PSS as it is based on the SA, which itself is a polyelectrolyte with positive surface charge, and then it was thoroughly washed with water.…”
Section: Methodsmentioning
confidence: 99%
“…Various filtration porous commercial or in-house substrates based on aromatic polysulfonamide, polysulfone, polyactrinitrile, etc. (consisting of mechanically rigid materials) are usually selected, depending on the separation task, to develop such supported membranes [ 12 , 68 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations